Designing Modular Cell-free Systems for Tunable Biotransformation of l-phenylalanine to Aromatic Compounds - Yang, Chen; Liu, Yushi; Liu, Wan-Qiu; Wu, Changzhu; Li, Jian (Frontiers in Bioengineering and Biotechnology, 2021)
Cell-free systems have been used to synthesize chemicals by reconstitution of in vitro expressed enzymes. However, coexpression of multiple enzymes to reconstitute long enzymatic pathways is often problematic due to resource limitation/competition (e.g., energy) in the one-pot cell-free reactions. To address this limitation, here we aim to design a modular, cell-free platform to construct long biosynthetic pathways for tunable synthesis of value-added aromatic compounds, using (S)-1-phenyl-1,2-ethanediol ((S)-PED) and 2-phenylethanol (2-PE) as models. Initially, all enzymes involved in the biosynthetic pathways were individually expressed by an E. coli-based cell-free protein synthesis (CFPS) system and their catalytic activities were confirmed. Then, three sets of enzymes were coexpressed in three cell-free modules and each with the ability to complete a partial pathway. Finally, the full biosynthetic pathways were reconstituted by mixing two related modules to synthesize (S)-PED and 2-PE, respectively. After optimization, the final conversion rates for (S)-PED and 2-PE reached 100% and 82.5%, respectively, based on the starting substrate of L-phenylalanine. We anticipate that the modular cell-free approach will make a possible efficient and high-yielding biosynthesis of value-added chemicals.